Can neck circumference predict cardiometabolic risk factors? A prospective cross-sectional study - Kaner, Gulsah; Gulden Pekcan, Ayla; Tel Adıguzel, Kubra; Seremet Kurklu, Nilgun; Pamuk, Gulseren (Progress in Nutrition, 2018)
Background and aim: This study aims to evaluate the association between neck circumference (NC) and several cardio-metabolic risk parameters, to compare it with some anthropometric variables. Methods: A total of 331 women, aged 20-49 years were recruited. Anthropometric measurements (body weight, height, waist and neck circumferences) and biochemical parameters [serum fasting blood glucose (FBG), fasting blood insulin (FBI), triglycerides, high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), and fibrinogen] were collected. Homeostasis model assessment-estimated IR (HOMA-IR) was calculated. Results: According to World Health Organization criteria, percentages of women with normal weight, overweight, obese and morbidly obese were 14.2%, 31.7%, 44.7%, 7.9%, respectively. Seventy-one percent of women had NC less than 37 cm, while that of twenty-nine percent of the women had higher. NC was moderately correlated with BMI, WC, FBI, HOMA-IR, and fibrinogen. A positive weak correlation was found between NC and FBG (p=0.031), TG (p=0.000), and LDL cholesterol (p=0.016). Moreover, a negative weak correlation was found between NC and HDL cholesterol (p= 0.000). A positive relationship between plasma fibrinogen and body weight (r=0.222), BMI (r=0.242), WC (r=0.187), TG (r=0.124), and LDL cholesterol (r=0.118) were detected whereas a negative relationship were found between HDL cholesterol and plasma fibrinogen (r=- 0.119) levels. Conclusion: A significant relation is existent between neck circumference and cardio-metabolic risk factors. NC could be used, it is easy to implement, an effective anthropometric measurement to the prediction of cardio-metabolic risks. Its usage together with anthropometric measurements such as waist and hip circumferences, waist-hip ratio and BMI which are widely used to determine cardio-metabolic risks can provide clinical benefits.